Elizabeth Cady Stanton, feminist as thinker : a reader in documents and essays - DuBois, Ellen Carol, 1947-; Cándida Smith, Richard (New York University Press, 2007)
More than one hundred years after her death, Elizabeth Cady Stanton still stands-along with her close friend Susan B. Anthony-as the major icon of the struggle for women's suffrage. In spite of this celebrity, Stanton's intellectual contributions have been largely overshadowed by the focus on her political activities, and she is yet to be recognized as one of the major thinkers of the nineteenth century. Here, at long last, is a single volume exploring and presenting Stanton's thoughtful, original, lifelong inquiries into the nature, origins, range, and solutions of women's subordination.